2013
DOI: 10.1152/ajpgi.00052.2013
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical regulation of ChAT and nNOS expression in animal models of Crohn's colitis and ulcerative colitis

Abstract: Morphological and functional changes in the enteric nervous system (ENS) have been reported in inflammatory bowel disease. We examined the effects of inflammation on the expression of choline acetyltransferase (ChAT) and nNOS in the muscularis externae of two models of colonic inflammation, trinitrobenzene sulfonic acid (TNBS)-induced colitis, which models Crohn's disease-like inflammation, and DSS-induced colitis, which models ulcerative Colitis-like inflammation. In TNBS colitis, we observed significant decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 57 publications
9
43
0
7
Order By: Relevance
“…Our results demonstrated that the number of cholinergic (ChAT-IR excitatory muscle motor and interneurons) and nitrergic (NOS-IR inhibitory muscle motor and interneurons) neurons in the myenteric plexus were unaltered in the distal colon of Winnie mice. These results are consistent with findings in rats with DSS-induced colitis (Winston et al 2013) and in patients with ulcerative colitis (Neunlist et al 2003). Further studies are needed to investigate the gene expression of proteins regulating the synthesis of ACh and NO which can be altered, even though the number of neurons is not changed, leading to intestinal dysmotility (Winston et al 2013).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our results demonstrated that the number of cholinergic (ChAT-IR excitatory muscle motor and interneurons) and nitrergic (NOS-IR inhibitory muscle motor and interneurons) neurons in the myenteric plexus were unaltered in the distal colon of Winnie mice. These results are consistent with findings in rats with DSS-induced colitis (Winston et al 2013) and in patients with ulcerative colitis (Neunlist et al 2003). Further studies are needed to investigate the gene expression of proteins regulating the synthesis of ACh and NO which can be altered, even though the number of neurons is not changed, leading to intestinal dysmotility (Winston et al 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Some studies reported increase, while others reported decrease or no change in the number of myenteric neurons in tissues from animal models of intestinal inflammation and from IBD patients (Table 2). Decreased number of neurons in the myenteric plexus in both wholemount preparations and cross-sections was reported in most animal models of chemically-induced intestinal inflammation, except a study reporting no changes in wholemount preparations and crosssections of the colon from rats with DSS-induced colitis (Winston et al 2013). In human tissues, most of the studies were performed in transverse or cross-sections showing either increase, decrease or no change in the number of myenteric neurons (Table 2).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[6,12]. В большинстве работ, выполненных в по-следние десятилетия, для выявления структур ЭНС применяют гистологические [4], гисто-химические [14], иммуногистохимические (ИГХ) [15] и иммунофлуоресцентные (ИФ) методы [8,9,16]. ИГХ и ИФ методы позволя-ют оценивать как нейроны различных мор-фофункциональных типов и глиальные клет-ки, так и их отростки, не выявляемые при ру-тинном гистологическом окрашивании.…”
Section: Introductionunclassified